The Effect Of Mental Exercises On The Development of Visual – Spatial Attention According to WAFR For Some Al Zewra Soccer Players - Yousif, Ali (Journal of Physical Education, 2016)
The importance of the research lies in the great development in psychological measurements and tests that help the athlete in reaching the his peak performance. The problem of the researcher lies in answering the following question; will visual – special attention of soccer players develop after applying spatial mental training exercises during their daily training session? The aim of the research included identifying the visual – spatial attention in some Al Zewra soccer players, designing mental exercise for developing this attention, and identifying the effect of these exercises on visual – spatial attention. The researcher hypothesized significant statistical differences between pre and posttests in visual – spatial attention for Al Zewra soccer players. The researchers used the experimental method and the subjects were Al zewra soccer players. The VTS tests and WAFR tests were conducted on the subjects to measure visual – Spatial attention. The data was collected and treated using proper SPSS to come up with the conclusions and recommendations.